Sync or sink? Interpersonal synchrony impacts self-esteem - Lumsden, Joanne; Miles, Lynden K.; Macrae, C. Neil (Frontiers in Psychology, 2014)
Synchronized behaviour has significant social influence both in terms of everyday activities (e.g., walking and talking) as well as via more historical contexts (e.g., cultural rituals). Grounded in the science of coordination dynamics, previous research has revealed that interpersonal synchrony has numerous affiliative and pro-social consequences, such as enhanced rapport, cooperation, and social-cognitive functioning. The current study sought to explore the impact of intentional synchrony versus asynchrony on an individual’s self-esteem and their feelings of social connection with a partner. The results revealed that individuals felt better about themselves following a period of synchronous compared to asynchronous movement, while they also perceived a greater self-other overlap with their partner. These findings not only extend previous research on social connections following interpersonal synchrony, but also provide the first demonstration of an influence on self evaluations. Overall, it appears that moving in time with others may result in us feeling better about ourselves compared to moving to our own rhythm.